Importance of rate control or rate regulation for improving exercise capacity and quality of life in patients with permanent atrial fibrillation and normal left ventricular function: a randomised controlled study. Issue 2 (1st February 2001) - Levy, T; Walker, S; Mason, M; Spurrell, P; Rex, S; Brant, S; Paul, V
Abstract : OBJECTIVE: To determine the importance of rhythm regulation or rate control in patients with permanent atrial fibrillation (AF) and normal left ventricular function. PATIENTS AND INTERVENTIONS: Thirty six patients with a mixed fast and slow ventricular response rate to their AF were randomised to either His bundle ablation (HBA) and VVIR pacemaker (HBA group) or VVI pacemaker and atrioventricular modifying drugs (Med group). Outcomes assessed at one, three, six, and 12 months included exercise duration and quality of life. RESULTS: Exercise duration significantly improved from baseline in both groups. There was no difference in outcome between the groups (Med +40% v HBA +20%, p = NS). The heart rate profile on exercise was similarly slowed in both groups compared to baseline. Quality of life significantly improved in both treatment arms for the modified Karolinska questionnaire (KQ) (Med +50% v HBA +50%, p = NS) and the Nottingham health profile (NHP) (Med +40% v HBA +20%, p = NS). However, for the individual symptom scores of each questionnaire more were improved in the Med group (KQ-Med 6 improved v HBA 4, NHP-Med 3 v HBA 1). Left ventricular function was equally preserved by both treatments during follow up. CONCLUSION: In these patients control of ventricular response rate with either HBA + VVIR pacemaker or atrioventricular modifying drugs + VVI pacemaker will lead to a significant improvement in exercise duration and quality of life. Rhythm regulation by HBA did not confer additional benefit, suggesting rate control alone is necessary for the successful symptomatic treatment of these patients in permanent AF.